PRODUK PEMBIAYAAN WISATA RELIGI HAJI PADA KOPERASI DALAM PERSPEKTIF HUKUM POSITIF DAN HUKUM EKONOMI SYARIAH - Achmad Otong Busthomi; Wasman .; Nurul Farichah (UIN Siber Syekh Nurjati Cirebon, 2018)
Abstract The large number interest of community in performing the hajj became one of the reference for Koperasi Nusantara in innovating the financing product. This product can be used for members of Koperasi Nusantara with some terms and conditions that have been determined. In financing, Koperasi Nusantara usesmurabaha financing. On the other side there should be a guarantee given to this community that there is portion number of Hajj and SPPH.This case study uses qualitative research method with descriptive approach that aims to get accurate data about financing in hajj. Techniques of collecting data used in this study are observation, interview and documentation. The collected data is analyzed by using qualitative analysis method which is done logically and systematically. Koperasi Nusantara as a savings and loan cooperative (KSP) that presents the product of religious tourism hajj financing enough to attract the attention of the public. In practice, however, this financing is in contrast to (PMA) no. 24 of 2016 on Amendment to Regulation of the Minister of Religious Affairs no. 30 Year 2013 concerning Banks Receiving Deposit Fees for Hajj Implementation that financing with the type of bailout had been prohibited. Keywords: Financing, Hajj, Mechanism, Murabahah and Policy. Abstrak Besarnya minat masyarakat dalam menunaikan ibadah haji menjadi salah satu acuan bagi Koperasi Nusantara dalam menginovasikan produk pembiayaan. Di dalam pembiayaan ini Koperasi Nusantara menggunakan pembiayaan murabahah. Bukan hanya itu, dalam pembiayaan ini juga harus ada jaminan yang diberikan kepada pihak koperasi yaitu berupa nomor porsi haji dan SPPH. Jenis penelitian ini adalah case study (studi kasus). Teknik pengumpulan data yang dilakukan adalah obeservasi, wawancara dan dokumentasi. Data-data yang terkumpul kemudian dianalisis dengan menggunakan metode analisis kualitatif normatif yang dilakukan secara logis dan sistematis. Koperasi Nusantara sebagai koperasi simpan pinjam (KSP) yang menghadirkan produk pembiayaan wisata religi haji cukup menarik perhatian masyarakat luas. Namun dalam prakteknya pembiayaan ini bertolak belakang dengan (PMA) No. 24 Tahun 2016 tentang Perubahan Atas Peraturan Menteri Agama No. 30 Tahun 2013 tentang Bank Penerima Setoran Biaya Penyelenggaraan Ibadah Haji bahwa pembiayaan dengan jenis talangan haji telah dilarang. Kata Kunci: Pembiayaan Wisata Religi Haji, Mekanisme, Murabahah dan Kebijakan.